Global city region governance and multicentered development: a North American perspective. (June 2015) - Kantor, Paul; Nelles, Jen
The impact of governance on multicentered development is examined by surveying the political responses of two leading North American global city regions (GCRs): New York and Toronto. Although both GCRs have experienced very similar policy tensions during recent decades, their process of economic restructuring is strongly mediated by four systemic features in regional governance: concentration of political authority, prevailing social cleavages, civic group resources, and intergovernmental coordination. Differences in these characteristics are found to influence collective action to manage tensions in three major policy areas. Their impact is not entirely cumulative, however. Even though there is evidence that having more of certain governing attributes enhances the possibilities for joint intervention on a regional scale, interaction among system components affects forms of intergovernmental collaboration. Further, the impact of governance systems on collective action also varies with policy area.